2017
DOI: 10.4103/aer.aer_30_17
|View full text |Cite
|
Sign up to set email alerts
|

To evaluate the efficacy of fentanyl and dexmedetomidine as adjuvant to ropivacaine in brachial plexus block: A double-blind, prospective, randomized study

Abstract: Context:Anesthesia and analgesia for surgeries to the upper extremity are commonly provided using brachial plexus anesthesia. There are limited or almost no studies comparing the use of ropivacaine with fentanyl to ropivacaine with dexmedetomidine.Aims:To compare the efficacy of fentanyl and dexmedetomidine as adjuvants to ropivacaine for brachial plexus block among patients undergoing upper limb orthopedic surgeries.Settings and Design:This was a prospective, randomized, double-blinded study.Subjects and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…This may be due to the use of ropivacaine rather than bupivacaine as ropivacaine has a longer duration of action, and the effect of adjuvants may not appear. [ 15 ] Furthermore, our results shows that there is statistically difference between fentanyl group, dexmedetomidine group, and bupivacaine group as regards to intraoperative HR with low HR among fentanyl group which can be explained by association of fentanyl with a vagus nerve-mediated bradycardia. This differs from Manohar and Prakash that shows lower HRs with dexmedetomidine group than fentanyl, and this difference may be due to larger number of patients in their study with use of smaller doses of fentanyl (50 mg only).…”
Section: Discussionmentioning
confidence: 74%
“…This may be due to the use of ropivacaine rather than bupivacaine as ropivacaine has a longer duration of action, and the effect of adjuvants may not appear. [ 15 ] Furthermore, our results shows that there is statistically difference between fentanyl group, dexmedetomidine group, and bupivacaine group as regards to intraoperative HR with low HR among fentanyl group which can be explained by association of fentanyl with a vagus nerve-mediated bradycardia. This differs from Manohar and Prakash that shows lower HRs with dexmedetomidine group than fentanyl, and this difference may be due to larger number of patients in their study with use of smaller doses of fentanyl (50 mg only).…”
Section: Discussionmentioning
confidence: 74%
“…3 ). And adding dexmedetomidine to ropivacaine obviously decreased the time to sensory block onset both in groups with dosage greater [ 12 , 14 , 16 21 , 23 ] (MD, −2.97 minutes, 95% CI −4.94 to −1.01 minutes, I 2 = 86%; P = .003) and less [ 13 , 15 , 22 ] (MD, −6.96 minutes, 95% CI −11.85 to −2.06 minutes, I 2 = 86%; P = .005) than 50 μg (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dexmedetomidine and fentanyl have been used as adjuvant to local anesthetics in different surgeries to provide superior analgesia and to improve the duration of the block [ 9 11 ]. One study on lower limbs surgery showed a better efficacy with dexmedetomidine [ 12 ].…”
Section: Introductionmentioning
confidence: 99%